Ethical Principles in Personal Protective Equipment Inventory Management Decisions and Partnerships Across State Lines During the COVID-19 Pandemic. (March 2022) - Merchant, Tazim; Hormozian, Sean; Smith, Roger S.; Pendergrast, Tricia; Siddiqui, Aliza; Wen, Zhaoyang; Sheldon, Mark
The COVID-19 pandemic created unprecedented strain on the personal protective equipment (PPE) supply chain. Given the dearth of PPE and consequences for transmission, GetMePPE Chicago (GMPC) developed a PPE allocation framework and system, distributing 886 900 units to 274 institutions from March 2020 to July 2021 to address PPE needs. As the pandemic evolved, GMPC made difficult decisions about (1) building reserve inventory (to balance present and future, potentially higher clinical acuity, needs), (2) donating to other states/out-of-state organizations, and (3) receiving donations from other states. In this case study, we detail both GMPC's experience in making these decisions and the ethical frameworks that guided these decisions. We also reflect on lessons learned and suggest which values may have been in conflict (eg, maximizing benefits vs duty to mission, defined in the context of PPE allocation) in each circumstance, which values were prioritized, and when that prioritization would change. Such guidance can promote a values-based approach to key issues concerning distribution of PPE and other scarce medical resources in response to the COVID-19 pandemic and related future pandemics.